Splenic Involvement in Hereditary Hemorrhagic Telangiectasia - Susumu Takamatsu; Kota Sato; Shunsuke Kato; Hiroto Nagano; Shunro Ohtsukasa; Yasuyuki Kawachi (Case Reports in Medicine)
A 33-year-old man who presented with prolonged epigastric pain was referred to our hospital. He had experienced recurrent epistaxis and had a family history of hereditary hemorrhagic telangiectasia. Computed tomography and magnetic resonance imaging revealed splenomegaly and a 9 cm hypervascular mass in his spleen. Computed tomography also showed a pulmonary arteriovenous malformation and heterogeneous enhancement of the liver parenchyma, suggesting the presence of arteriosystemic shunts and telangiectases. Based on these findings, the patient was definitely diagnosed with hereditary hemorrhagic telangiectasia according to Curaçao criteria. He underwent splenectomy, and his symptoms disappeared after surgery. Pathological examination of the resected specimen revealed that the hypervascular lesion of the spleen was not a tumor but was composed of abnormal vessels associated with hereditary hemorrhagic telangiectasia. Symptomatic splenic involvement may be a rare manifestation of hereditary hemorrhagic telangiectasia but can be revealed by imaging modalities.